A cidade contra a cidade: trajetórias curitibanas em conflito - Lima, Rosirene Martins (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2010)
The current urban agenda prioritizes the inclusion of cities in the global market. Urban policies targeted on the criteria of competitiveness and sustainability, value certain spaces over others, forcing residents who can not pay for this city to move to outskirts areas, “outside” the center of the model. In Curitiba the process sharpened the contradictions in the occupation of the city. Urban planning was effective, in order to keep “poverty” away from Curitiba, inducing a “selective” and “segregated” occupation. This work aims to reflect on the strategies of a community of recyclable material, called the occupation illegal to live in the city. These “stigmatized” areas explain the contradictions of urban policy, producing “modernization of poverty.”